2015
DOI: 10.1111/epi.12946
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibition suppresses established epilepsy in a mouse model of cortical dysplasia

Abstract: Summary Objective Hyperactivation of the mechanistic target of rapamycin (mTOR) pathway has been demonstrated in human cortical dysplasia (CD) as well as in animal models of epilepsy. While inhibition of mTOR signaling early in epileptogenesis suppressed epileptiform activity in the neuron subset-specific Pten knockout (NS-Pten KO) mouse model of CD, the effects of mTOR inhibition after epilepsy is fully established were not previously examined in this model. Here, we investigated whether mTOR inhibition supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 43 publications
5
78
1
1
Order By: Relevance
“…Rapamycin has been shown to inhibit immune responses in normal animals (Lu et al, 2015) and can attenuate epilepsy-associated inflammation (Brewster et al, 2013; Nguyen et al, 2015; Shima et al, 2015), leading us to ask whether rapamycin affected the activation state of astrocytes following SE. Astrocytic activation was first assessed by measuring the soma area of astrocytes in the dentate hilus.…”
Section: Resultsmentioning
confidence: 99%
“…Rapamycin has been shown to inhibit immune responses in normal animals (Lu et al, 2015) and can attenuate epilepsy-associated inflammation (Brewster et al, 2013; Nguyen et al, 2015; Shima et al, 2015), leading us to ask whether rapamycin affected the activation state of astrocytes following SE. Astrocytic activation was first assessed by measuring the soma area of astrocytes in the dentate hilus.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in genes that encode proteins within the PI3K-AKT-mTOR cascade, such as activating PI3K or AKT mutations or loss-of-function PTEN or TSC2 mutations (TABLE 1), lead to constitutive mTOR signalling activation and result in common phenotypic features of MCDs, including changes in cell morphology and cellular enlargement (cytomegaly), changes in motility that lead to disorganized cortical lamination, neuronal hyperexcitability, and seizures. Although mTOR-independent functions of PI3K or AKT mutations can also contribute to changes in brain structure, the net cellular effects of mutations affecting the PI3K-AKT-mTOR pathway seem to funnel through mTOR as a common signalling node, as evidenced by in vitro and in vivo data demonstrating that structural alterations (increased cell size, dendritic arborization, and cortical lamination) and functional effects (neuronal hyperexcitability and seizures) of these mutations can be reversed by pharmacological mTOR inhibition with rapamycin or related compounds 35,36 Tuberous sclerosis complex The classic mTORopathy is tuberous sclerosis complex (TSC), a multisystem disorder that results from inherited or sporadic loss-of-function mutations in TSC1 or TSC2 and affects the brain, skin, eyes, kidneys, heart and lungs 37 . Nearly 80% of patients with TSC have a form of FCD known as cortical tubers.…”
Section: Megalencephalymentioning
confidence: 99%
“…Brain specimens obtained from patients with PTEN mutations show altered cyto architecture and increased AKT activity 55 . Moreover, an in vitro study has demonstrated that PTEN mutations can cause increased S6 protein phosphorylation owing to mTORassociated downstream activation, and administration of mTOR inhibitors rescues the cellular abnormalities and seizures 35 . Mutations in TBC1D7 (REF.…”
Section: Pten Mutationsmentioning
confidence: 99%
“…PTEN-induced hyperactivation of the mTOR pathway mediates many of the abnormalities evident in animal models (Kwon et al, 2003; Zhou et al, 2009; Nguyen et al, 2015; Matsushida et al, 2016). mTOR is a major target of the PI3K-Akt pathway, activating signaling cascades that regulate neuronal proliferation, survival, growth and plasticity (Switon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%